Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Lingkungan Kerja Kecamatan Salopa Kabupaten Tasikmalaya - Haikal Pikri; Arga Sutrisna; Barin Barlian (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze the influence of training and work motivation on employee performance in the working environment of Salopa District, Tasikmalaya Regency. Training and work motivation play a crucial role in enhancing employee performance in the public sector, including at the district level. The research employed a quantitative approach, involving employees as respondents in Salopa District. The collected data were analyzed using descriptive statistical techniques and regression analysis to identify the relationship between training, work motivation, and employee performance. The results of the study indicate that training has a positive and significant impact on employee performance in the working environment of Salopa District. With relevant and effective training, employees have the opportunity to develop the skills, knowledge, and competencies required to perform their tasks more effectively. Training can enhance the efficiency, effectiveness, and professionalism of employees in providing services to the community. Furthermore, work motivation also has a significant influence on employee performance. Motivational factors such as recognition, rewards, incentives, organizational support, and career development opportunities can influence employees’ attitudes, work enthusiasm, and dedication to their jobs. Motivated employees tend to have higher performance levels and contribute positively to the achievement of organizational goals